Malaria and malnutrition in tribal areas of India: implications for paediatric health - Verma, Anil Kumar; Shrivastava, Suyesh; Saxena, Nishant (Frontiers in Gastroenterology, 2025)
Malaria and malnutrition (undernutrition) are associated with poor health and poverty. Undernutrition affects children’s general development, particularly the formation of a healthy immune system. Malaria parasites infect and propagate within vulnerable populations, causing anemia, fever, and, if ignored, death. Furthermore, frequent exposure to malaria and intestinal infections alters gut flora, exacerbating malnutrition caused by poor digestion and malabsorption of ingested food. In India, Tribal people are trapped in a vicious cycle of hunger and infectious diseases, such as malaria, due to inadequate diet, unsanitary practices, water quality, sanitation, attitude, and lack of access to healthcare facilities. Therefore, an integrated approach that caters to the nutritional and malaria-specific needs of the tribal population is required to eliminate malaria from tribal areas of India. This mini-review discusses the problems and probable solutions for the control and elimination of malaria in the tribal areas in India.